Jurnal Penyuluhan: Efektivitas Program Beasiswa untuk Meningkatkan Prestasi Mahasiswa (Kasus pada Mahasiswa Penerima Beasiswa Beastudi Etos di Jabodetabek - Mardiyanti Mardiyanti, Ninuk Purnaningsih, Prabowo Tjitropranoto (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
For achieve educational equity, government, private and non government organization provide scholarships. Scholarships are awarded as an effort to empower the recipients.